Racism Portrayed in I Am Thunder and The Hate U Give - Manurung, Ayub; Pardede, Martha; Sumbayak, Desri Maria (LingPoet: Journal of Linguistics and Literary Research, 2021)
This research is intended to describe the racism that found in I Am Thunder; to describe the racism that found in The Hate U Give; and to find out the similarities and differences of racism that found in I Am Thunder and The Hate U Give. This research used a descriptive qualitative method, which was done by collecting, grouping, and analyzing the research data. The data in this research were dialogue and event, which are related to racism in both of novels. The data were collected by reading the both of novels and compare the both of novels. Based on the data analysis it was found that four forms of racism were found in both of novels they are stereotype, prejudice, rejection and discrimination. After analyzing racism by four forms of racism, the writer finally found similarities and differences. Both of the main character in these novels treated badly in society because of their race, they can’t be their own selves in public and should fight against racism, but the main characters have different race, Muzna is a Britain Pakistani while Starr is a Black American. The prejudice and stereotype to these cultures are different. People thought that Britain Pakistani deals with terrorist and ISIS while Black American deals with crime, thug and gangster.